Is J.S. Mill's Account of Free Speech Sustainable in the Age of Social Media? - Chellappah, Nevin (Stance: an international undergraduate philosophy journal, 2022)
In this paper, I examine whether John Stuart Mill’s account of free speech can survive three main challenges posed by social media. First, I consider the problem of social media failing to distinguish between emotive and factual language. Second, I look at the problem of algorithms creating moralism. I then turn to a potential objection to my first two challenges. The objection elucidates the benefits of social media’s emotional and algorithmic character, amplifying arguments and increasing public engagement. However, I take issue with this objection on consequentialist terms. I finally return to the third challenge, where I focus on how anonymity removes the consequences to our words; I contend that this final failure is the ultimate reason why Mill’s account cannot persist in the modern age. In conclusion, I argue that Mill’s account cannot withstand the problems posed by social media.